Apixaban use in an atrial fibrillation patient with double mechanical heart valves: a case report. Issue 7 (31st July 2021) - Eom, Jae Young; Shin, Je Kyoun; Kwon, Chang Hee
Abstract: Background: Warfarin is the only approved oral anticoagulant for long-term prophylaxis against valve thrombosis and thromboembolism in patients with mechanical heart valves. To date, apixaban for patients with double (aortic and mitral) mechanical heart valves has not been reported in the literature. Case summary: We report the case of a 50-year-old female who underwent double (aortic and mitral) mechanical valve replacement in February 2017. Warfarin was prescribed after mechanical valve replacement. However, she complained of side effects of warfarin, including tingling sensation and numbness of legs, urticaria, skin rash, and nausea and voluntarily stopped taking medication. In December 2018, she was admitted to the emergency room due to ongoing chest pain. Coronary angiogram revealed embolic myocardial infarction at the left circumflex coronary artery. Nevertheless, she continued to refuse to take warfarin after anticoagulant therapy for coronary artery embolism. Given the patient's objection, we prescribed apixaban 5 mg b.i.d. since February 2019. When she was diagnosed with atrial fibrillation in April 2020, no intracardiac thrombosis was confirmed on computed tomography and electrical cardioversion was performed safely. While on apixaban, no evidence of prosthetic valve thrombosis or thrombo-embolic events was observed during a 24-month period. Conclusion: We report the efficacy and safety of apixaban in a patient with atrial fibrillation and double mechanical heart valves for preventing prosthetic valve thrombus and systemic embolism.